On the Physical-Chemical Nature of Solvent Polarizability and Dipolarity - Caroli-Rezende, M; Mera-Adasme, R; Dominguez-Caru, M (Elsevier B.V., 2020)
The positive solvatochromism of three dyes, with a spectral behavior strongly dependents on the medium dipolarity/polarizability, was studied theoretically. Both a polarizable continuum-solvent model (CSM) and explicit solvent molecules were employed to model solvent effects. The CSM approach, coupled with ten different TDDFT methods, yielded unsatisfactory results in eleven solvents. The explicit-solvation calculations, thought of much higher computational cost, yielded excellent results. As CSM schemes are known correctly model non-specific electrostatic effects, our results indicate that the traditionally considered non-specific nature of solvent dipolarity needs to be reconsidered, requiring the explicit consideration of the solute-solvent interactions for their accurate theoretical description. © 2018 Elsevier B.V.